Discovery and characterization of 25 new quasars at 4.6 < z < 6.9 from wide-field multiband surveys - Belladitta, Silvia; Bañados Torres, Eduardo; Xie, Zhang-Liang; Decarli, Roberto; Onorato, Silvia; Yang, Jinyi; Bischetti, Manuela; Onoue, Masafusa; Loiacono, Federica; Martínez-Ramírez, Laura N.; Mazzucchelli, Chiara; Davies, Frederick B.; et al. (Astronomy and astrophysics, 2025)
Luminous quasars at z>4 provide key insights into the early Universe. Their rarity necessitates wide-field multiband surveys to efficiently separate them from the main astrophysical contaminants (i.e., ultracool dwarfs). To expand the sample of high-z quasars, we conducted targeted selections using optical, infrared, and radio surveys, which we complemented by literature-based quasar candidate catalogs. We report the discovery of 25 new quasars at 4.6<z<6.9 (six at z≥6.5), with M1450 between −25.4 and −27.0. We also present new spectra of six z>6.5 quasars we selected, but whose independent discovery has already been published in the literature. Three of the newly discovered quasars are strong radio emitters (L1.4 GHz = 0.09−1.0×10 34 erg s −1 Hz−1). One source at z = 4.71 exhibits typical blazar-like properties, including a flat radio spectrum, a radio loudness of ∼1000, and multifrequency variability. It was also detected by SRG/eROSITA X-ray telescope (f 0.2−2.3 keV∼1.3×10 −13 erg s −1< cm −2). In addition, for seven 6.3<z<6.9 quasars, we present near-infrared spectroscopy and estimated the central black hole mass from their C IV and Mg II broad emission lines. Their masses (log[M BH,MgII] = 8.58−9.14 M⊙) and Eddington ratios (λ Edd,MgII = 0.74−2.2) are consistent with other z>6 quasars reported in the literature. A z = 6.3 quasar exhibits a velocity difference of approximately 9000 km s −1 between the C IV and Mg II emission lines. This means that it is one of the most extreme C IV outflows currently known. The sample also includes three high-ionization broad absorption line (HiBAL) quasars. One of these quasars shows potential evidence of an extremely fast outflow feature that reaches 47 000 km s -1.
Gesehen am 17.12.2025